Anti-Müllerian hormone in type 2 and gestational diabetes during the second half of pregnancy: relationship with sexual steroid levels and metabolic parameters. (1st February 2018) - Villarroel, Claudio; Salinas, Abril; López, Patricia; Kohen, Paulina; Rencoret, Gustavo; Devoto, Luigi; Codner, Ethel
Abstract: Hyperandrogenemia and hyperinsulinemia are observed in women with diabetes during pregnancy. The effect of diabetes on anti-Müllerian hormone (AMH) levels during pregnancy is unclear. The aim of this study was to determine the AMH levels in women with type 2 diabetes (T2D) and gestational diabetes (GD) compared to healthy (C) pregnant women during the second half of gestation. A prospective study of 69 pregnant women with T2D ( N : 21), GD ( N : 24) and C ( N : 24) were followed up during the second half of pregnancy. Clinical assessments and blood samples were collected at 26.7 (25–27.8); 34 (32–34.9) and 37.5 (37–40) weeks of gestation. AMH, sexual steroids, insulin, homeostatic model assessment of insulin resistance, HbA1c levels were measured. AMH levels were similar between T2D, GD and C ( p  = .07). A decline of AMH levels during the second half of gestation was observed in the three groups ( p  < .0001). AMH levels were negatively associated with age ( p  < .001). A positive association between AMH and testosterone ( p  < .05) was found in all groups. A progressive decline of AMH levels is observed in diabetic and healthy women during the second half of pregnancy. Testosterone levels are an independent factor that influences AMH levels during pregnancy. However, AMH levels are not affected by the presence of diabetes during gestation.